Rehabilitation of the hand and upper extremity - Terri M. Skirven (Philadelphia : Elsevier, 2021)
Long recognized as an essential reference for therapists and surgeons treating the hand and the upper extremity, Rehabilitation of the Hand and Upper Extremity helps you return your patients to optimal function of the hand, wrist, elbow, arm, and shoulder. Leading hand surgeons and hand therapists detail the pathophysiology, diagnosis, and management of virtually any disorder you're likely to see, with a focus on evidence-based and efficient patient care. Extensively referenced and abundantly illustrated, the 7th Edition of this reference is a "must read" for surgeons interested in the upper extremity, hand therapists from physical therapy or occupational therapy backgrounds, anyone preparing for the CHT examination, and all hand therapy clinics.
Keywords: Arm Injuries rehabilitation; Hand Surgery Patients Rehabilitation; Hand Injuries rehabilitation